THE EFFECT OF INTELLECTUAL CAPITAL ON PROFITABILITY AND STOCK RETURN (CASE STUDY OF JAKARTA ISLAMIC INDEX FOR 2013-2018 PERIOD) - Gabriella Jodie Adhama; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
Intellectual capital is the creation of company value added represented by employees with all the potential and capabilites they have. This study aims to analyze the effect of Intellectual Capital, profitability as an intervening variable on Islamic stock returns on the Jakarta Islamic Index (JII). Sampling of 14 issuers was carried out using purposive sampling technique. The method used is path analysis with a maximum likelihood model. Intellectual capital has a positive effect on ROA, ROA has no significant effect on returns, Intellectual Capital has a significant positive effect on returns directly, Intellectual Capital indirectly has insignificant effect on returns for the 2013-2018 period. Based on these results, the issuer company can disclose reports related to intellectual capital from the company. Research on intellectual capital using intervening variables in Indonesia still tends to be limited, besides that the writer also uses path analysis with the maximum likelihood model. In this study robustness tests were also conducted to test the resilience of the variables used.Keywords: intellectual capital, ROA, return, JII, path analysis